DEVELOPMENT OF AUDIO-VISUAL LEARNING MEDIA ON LOCAL HISTORICAL FIGURE HAUSMAN BABOE OF CENTRAL KALIMANTAN - Isabella; Susanto, Yudi; Sumiatie (ISTORIA : Jurnal Pendidikan dan Ilmu Sejarah, 2025)
This study aimed to produce history teaching materials in the form of an audio-visual media about the local historical figure Houman Baboe that was valid, effective, and suitable for enhancing the learning motivation of tenth-grade students at SMA Negeri 3 Palangka Raya. The development of the media employed the 4-D model (Define, Design, Develop, Disseminate) by Thiagarajan et al. (1974). Data were collected through interviews, documentation, and questionnaires administered to content experts, media experts, academic supervisors, and students. The validation results indicated that the media received a feasibility score of 79% from the content expert and 88.5% from the media expert, confirming its suitability for use. The implementation of the media in the learning process led to a significant increase in students’ motivation, with an average score of 87.93%, reflecting a 21.04% improvement compared to the pre-use stage. The audio-visual media titled Houman Baboe: Footprints and Contributions to Central Kalimantan was proven to be valid, effective, and appropriate as a local-based history teaching resource